TRANSFORMASI POSITIF JUAL BELI ONLINE DI ASTRO MOSLEM MOJOAGUNG KABUPATEN JOMBANG DALAM PERSPEKTIF EKONOMI ISLAM - Nur Husen, Mohamad; Analisa, Putri (TIJAROTANA : Jurnal Ekonomi dan Bisnis Syariah, 2025)
Digitalization is bringing conventional transactions into a digital ecosystem with the integration of technology that makes it easier for sellers and buyers, and reaches a wider market. In Islamic economics, there are muamalah activities, such as buying and selling, renting, and lending, which are regulated by religion for the public good. This research is a qualitative type through literature studies and field studies. This study classifies data based on research formulas. In the next stage, data processing or reference citation is carried out. In the implementation of field research, observations, documentation and interviews were carried out. The results of the study show that the use of online platforms by Astro Moslem brings positive digital transformation to the business world, where technology is used to expand the market and improve services to consumers without ignoring moral values in Islam. This study also shows that this online buying and selling model provides opportunities for Muslims to empower their economy through halal businesses, as well as encourage local economic growth based on sharia principles. Online buying and selling at Astro Moslem Mojoagung has increased accessibility for the public to obtain halal products easily and efficiently, in line with Islamic economic principles such as justice, transparency, and avoiding usury, gharar, and maysir. Overall, the transformation of online buying and selling at Astro Moslem Mojoagung has a positive impact on the Islamic economy by combining technological innovation and fair, transparent, and ethical economic principles.